Task force: development policy and strategies in East Asia by the case of chinese environment policy - Heberer, Thomas; Senz, Anja-Désirée (Duisburger Arbeitspapiere Ostasienwissenschaften, 2009)
This report approaches current domains of development and tension within China. It was elaborated by students in the frame of a "Task Force Seminar" in cooperation with the German Federal Ministry for the Environment, Nature Conservation and Nuclear Safety (BMU). It addresses the issues of strategies for an environmentally friendly development in China, including the position of China in international environmental negotiations, biodiversity in China, financial incentives for the promotion of renewable energy, the implementation of environmental policies on the local level by the case study of water management, product responsibility and product safety as a societal demand with the options for consumer organization and articulation. At the end of each chapter, recommendations for the German-Chinese development cooperation will be given. -- Biodiversity ; consumer rights ; environmental issues ; development policy ; development cooperation ; implementation gap ; international environmental negotiations ; product security ; renewable energy ; technology transfer ; water management
Keywords: Arbeitspapier; Graue Literatur